KONTRIBUSI ENERGI TERBARUKAN DAN AKTIVITAS EKONOMI TERHADAP PERUBAHAN EMISI KARBON DI INDONESIA - Amanda, Rendi; Nurhayati, Nurhayati; Muhammad Yudhi Lutfi; Ni Putu Ayu Laksmi Subadra (Media Ekonomi, 2024)
This study examines the relationship between renewable energy consumption, urbanization, gross domestic product per capita, international trade, inflation, and CO2 emissions in Indonesia, factors commonly analyzed in the Environmental Kuznets Curve (EKC) hypothesis. This study uses a quantitative approach with annual time series data for Indonesia from 1990 to 2023, obtained from the World Bank. The analysis was conducted using a multiple linear regression model estimated using the Ordinary Least Squares (OLS) method with a significance level of 5%. The regression model was estimated and analyzed using EViews version 9.0. The results show that renewable energy consumption (REC) has a significant negative effect on CO₂ emissions, while urbanization (URB) and international trade (TRADE) have a significant positive impact on CO₂ emissions. The relationship between GDP per capita (GDPC) and CO₂ emissions shows a U-shaped pattern, not an inverted U as in the EKC hypothesis. Inflation (INF) has no significant effect on CO₂ emissions, indicating that the relationship is influenced by other factors such as fossil energy consumption and environmental policies. This finding emphasizes the need for a comprehensive approach to reducing CO₂ emissions, rather than relying solely on monetary policy or market mechanisms.